Habituation of glomerular responses in the olfactory bulb following prolonged odor stimulation reflects reduced peripheral input - Ogg, Mary C.; Bendahamane, Mounir; Fletcher, Max L. (Frontiers in Molecular Neuroscience, 2015)
Following prolonged odor stimulation, output from olfactory bulb (OB) mitral/tufted (M/T) cells is decreased in response to subsequent olfactory stimulation. Currently, it is unclear if this decrease is a function of adaptation of peripheral olfactory sensory neuron (OSN) responses or reflects depression of bulb circuits. We used wide-field calcium imaging in anesthetized transgenic GCaMP2 mice to compare excitatory glomerular layer odor responses before and after a 30-s odor stimulation. Significant habituation of subsequent glomerular odor responses to both the same and structurally similar odorants was detected with our protocol. To test whether depression of OSN terminals contributed to this habituation, olfactory nerve layer (ON) stimulation was used to drive glomerular layer responses in the absence of peripheral odor activation of the OSNs. Following odor habituation, in contrast to odor-evoked glomerular responses, ON stimulation-evoked glomerular responses were not habituated. The difference in response between odor and electrical stimulation following odor habituation provides evidence that odor response reductions measured in the glomerular layer of the OB are most likely the result of OSN adaptation processes taking place in the periphery.